Analisis Kualitas Pelayanan Bidang Administrasi Kependudukan di Kantor Kelurahan Bangkingan Kota Surabaya - Firmansyah, Wildan; Isbandono, Prasetyo (Jurnal Inovasi Administrasi Negara Terapan, 2025)
One of the community services provided by the Bangkingan Village Office, an organization under the Surabaya City Government, is population administration. This study set out to characterize the level of population administration services provided by the Bangkingan Village Office in Surabaya City. Descriptive study using a qualitative approach is the methodology employed. Documentation, interviews, and observation are the methods used to gather data. The data is tested using data reduction, data display, data collection techniques, and conclusion drafting. The focus of this research uses indicators of the five dimensions of public service quality according to Zeithaml in (Hardiyansyah, 2018), namely tangibel, reliability, responsiveness, assurance, and empathy. The results showed that the quality of service in the field of population administration at the Bangkingan Village Office in Surabaya City had fulfilled the four existing indicators. However, there is one indicator that is still not maximally fulfilled, namely tangibel. This is indicated in the aspect of the comfort of the population administration service place in Bangkingan Village which is still considered cramped, and the lack of provision of queuing chairs. Then in the aspect of ease of public access and the use of service aids, there is no signboard for other service rooms and computer facilities that still use old specifications.